SnO2–TiO2 hybrid nanofibers for efficient dye-sensitized solar cells. (July 2016) - Wali, Qamar; Bakr, Zinab H.; Manshor, Nurul Ain; Fakharuddin, Azhar; Jose, Rajan
Graphical abstract: Electrospun tin oxide multi-porous nanofibers simultaneously supporting improved dye-loading and charge transport are employed as photoanode in dye-sensitized solar cells with high photovoltaic conversion efficiency. Highlights: TiO2 nanoparticles are grown in SnO2 nanofibers pores. Nanofibers composite was employed as photoanode for dye sensitized solar cells. Synergistic photovoltaic parameters were observed. Best performing devices showed efficiency up to 8%. Abstract: Pristine SnO2 nanostructures typically result in low open circuit voltage ( V OC ) <500 mV due to the lower Fermi energy ( EF ) when employed as a photoanode materials in dye sensitized solar cells (DSSCs). On the other hand, the most successful photoanode material, i.e., TiO2 nanoparticle although provides a high V OC  ⩾ 800 mV result in poor charge collection owing to their inferior electron mobility ( μn ). Herein, we employ nanofiber–nanoparticle composite of SnO2 –TiO2 which showed similar V OC and short circuit current density ( J SC ) to a reference TiO2 based DSSCs. The nanocomposite developed here involves multi-porous SnO2 nanofibers characterized by a lower EF ; however, with higher μn and TiO2 nanoparticles of higher EF and lower μn . The TiO2 particles in the pores of SnO2 nanofibers were developed by TiCl4 treatment, whose concentration is optimized for the saturated J SC and V OC . The best performing DSSCs fabricated using the composite electrodes deliver power conversion efficiency (PCE) of ≈7.9% ( V OC  ≈ 717 mV; J SC  ≈ 21 mA cm −2 ), which is significantly higher than pure SnO2 photoanode with PCE ≈ 3.0% ( J SC  ≈ 14.0 mA cm −2 and V OC  ≈ 481 mV) at similar experimental conditions.